Strategi Pembebanan PLTS Off Grid untuk Peningkatan Kontinuitas Suplai Energi Listrik - Syafii Syafii; Yona Mayura; Muhardika Muhardika (Jurnal Rekayasa Elektrika, 2019)
Solar power plants using environmentally friendly technology in the process of harvesting energy from the sun can be a solution to the future electricity crisis so that it has been the most widely developed and reliable alternative. However, the conversion of solar energy depends on the availability and conditions of sunlight. In sunny conditions, the PV system can serve large loads while charging the battery to the maximum. While in cloudy weather conditions or at night, the PV system serves the load and without charge of the battery. The battery will discharge the stored energy until it runs out and the supply to the load will be cut off before the desired time. Therefore, research on PV system loading strategy is needed to increase the amount of electricity from solar energy and maintain the continuity of electricity supply to the load. The load power management strategy follows the conditions of sunny, cloudy, rainy or night time by considering the remaining capacity of the battery that can be used. Load installations are designed to consist of low, medium and high load installations. Simulation results show that the use of PV loading management strategies can increase the operating time of the PV system. When the remaining 15% battery capacity and PLN supply is available, the supply will be switched to PLN. The remaining 15% of PV battery capacity could be used to maintain electricity supply to a low load if the PLN supply interrupted. Thus the use of the charging strategy will increase the supply of electricity from renewable energy and improve the continuity of electricity supply.